2008
DOI: 10.1073/pnas.0810761105
|View full text |Cite
|
Sign up to set email alerts
|

TRPV6 is not required for 1α,25-dihydroxyvitamin D 3 -induced intestinal calcium absorption in vivo

Abstract: The requirement for TRPV6 for vitamin D-dependent intestinal calcium absorption in vivo has been examined by using vitamin D-deficient TRPV6 null mice and littermate wild-type mice. Each of the vitamin D-deficient animals received each day for 4 days 50 ng of 1,25-dihydroyvitamin D 3 in 0.1 ml of 95% propylene glycol:5% ethanol vehicle or vehicle only. Both the wild-type and TRPV6 null mice responded equally well to 1,25-dihydroxyvitamin D 3 in increasing intestinal calcium absorption. These results, along wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
52
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 92 publications
(54 citation statements)
references
References 24 publications
2
52
0
Order By: Relevance
“…Second, this idea is reinforced by the fact that although numerous investigations over many years have identified multiple components that are regulated by 1,25(OH) 2 D 3 and that contribute to calcium uptake, they have failed to identify a single component that upon deletion fully recapitulates the state of vitamin D deficiency. Trpv6 expression, for example, exerts a significant impact on calcium transport independent of its regulation by 1,25(OH) 2 D 3 , yet it fails upon deletion to block intestinal response to 1,25(OH) 2 D 3 (15,29). Overexpression of calbindin D9K, however, has no impact on intestinal calcium absorption, and Pmca1 has not been examined.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, this idea is reinforced by the fact that although numerous investigations over many years have identified multiple components that are regulated by 1,25(OH) 2 D 3 and that contribute to calcium uptake, they have failed to identify a single component that upon deletion fully recapitulates the state of vitamin D deficiency. Trpv6 expression, for example, exerts a significant impact on calcium transport independent of its regulation by 1,25(OH) 2 D 3 , yet it fails upon deletion to block intestinal response to 1,25(OH) 2 D 3 (15,29). Overexpression of calbindin D9K, however, has no impact on intestinal calcium absorption, and Pmca1 has not been examined.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, many of these genes have been genetically deleted in mice, providing the opportunity to assess whether they yield a vitamin D deficiency-type phenotype, although the lack of a complete vitamin D deficiency phenotype in mice containing deletions of S100g, Trpv6, or their combination and the more complex contributions of a gene network suggest that individual deletions may not reveal this type of deficiency phenotype (14,29). A number of genes regulated by 1,25(OH) 2 D 3 in addition to S100g, Trpv6, Atp2b1, and Cldn2 have been suggested to be involved in calcium regulation, although their primary function may be different.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This previous study together with microarray results indicated that TRPV6 is not required for vitamin D-induced intestinal calcium absorption and may not carry out a significant role in this process. These results obtained from CaBP-9k null and other calcium transport mutant mice illustrated that exact molecular events in the intestinal calcium transport in response to the active form of vitamin D are warranted to be elucidated (Kutuzova et al, 2008).…”
Section: Cabp-9k and Its Compensatory Mechanism In The Knockout Modelsmentioning
confidence: 92%
“…On the other hand, the requirement of TRPV6 for vitamin D-dependent intestinal calcium absorption in vivo was examined in vitamin D-deficient TRPV6 null and WT mice (Kutuzova et al, 2008). This previous study together with microarray results indicated that TRPV6 is not required for vitamin D-induced intestinal calcium absorption and may not carry out a significant role in this process.…”
Section: Cabp-9k and Its Compensatory Mechanism In The Knockout Modelsmentioning
confidence: 96%